2013
DOI: 10.1098/rspb.2013.1331
|View full text |Cite
|
Sign up to set email alerts
|

Environmental enrichment promotes neural plasticity and cognitive ability in fish

Abstract: Different kinds of experience during early life can play a significant role in the development of an animal's behavioural phenotype. In natural contexts, this influences behaviours from anti-predator responses to navigation abilities. By contrast, for animals reared in captive environments, the homogeneous nature of their experience tends to reduce behavioural flexibility. Studies with cage-reared rodents indicate that captivity often compromises neural development and neural plasticity. Such neural and behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
197
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 208 publications
(225 citation statements)
references
References 46 publications
5
197
1
2
Order By: Relevance
“…In zebrafish, i.e. Danio rerio, enhancement of the small captive environment with plastic plants and gravel increased forebrain cell proliferation [von Krogh et al, 2010] and, in Atlantic salmon (Salmo salar) , a similar enrichment that was also modified temporally increased the expression of NeuroD mRNA, a marker of early neuronal differentiation [Salvanes et al, 2013]. Neither of these studies distinguished between regions within the forebrain or in nonforebrain regions, so it is not clear whether the effect was specific.…”
Section: Physical Environmentmentioning
confidence: 87%
See 2 more Smart Citations
“…In zebrafish, i.e. Danio rerio, enhancement of the small captive environment with plastic plants and gravel increased forebrain cell proliferation [von Krogh et al, 2010] and, in Atlantic salmon (Salmo salar) , a similar enrichment that was also modified temporally increased the expression of NeuroD mRNA, a marker of early neuronal differentiation [Salvanes et al, 2013]. Neither of these studies distinguished between regions within the forebrain or in nonforebrain regions, so it is not clear whether the effect was specific.…”
Section: Physical Environmentmentioning
confidence: 87%
“…Among socially interacting trout, subordinate fish, which also showed low rates of cell proliferation, hesitated to approach food and ate less during feeding periods compared to dominant and isolated fish . Similarly, salmon [Salvanes et al, 2013] and zebrafish [von Krogh et al, 2010] raised in simple environments that inhibited forebrain cell proliferation were more tentative in venturing out of shelters or seeking food than fish raised in a complex environment that promoted cell proliferation. These negative correlations between forebrain cell proliferation and boldness parallel those found in rodents, where an experimental reduction of hippocampal neurogenesis inhibits exploratory behavior and induces anxiety behavior [Revest et al, 2009].…”
Section: Are Environmentally Induced Changes In Brain Cell Proliferatmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have found larger telencephalons in mobile fish foraging within spatially complex environments compared to fish that forage in less complex environments [Huber et al, 1997;Kotrschal et al, 1998;Pollen et al, 2007;Gonda et al, 2009Gonda et al, , 2011Costa et al, 2011]. Controlled laboratory studies have demonstrated that salmon [Kotrschal et al, 2012;Näslund et al, 2012;Salvanes et al, 2013] and zebra fish [von Krogh et al, 2010] show an increased telencephalon size when raised in spatially enriched environments compared to barren environments. Similarly, in Azorean rock pool blennies (Parablennius sanguinolentus) the variation in telencephalon size appears to be closely related to the spatial challenges associated with structurally complex environments [Costa et al, 2011].…”
Section: Introductionmentioning
confidence: 99%
“…As reviewed in Näslund and Johnsson (2014), there are several studies demonstrating the positive effects of environmental enrichment on welfare across many fish species. Compared with captive-held fish in barren environments, those provided with some form of enrichment have been found to have increased brain development (Marchetti and Nevitt, 2003;Kihslinger and Nevitt, 2006;von Krogh et al, 2010;Salvanes et al, 2013), reduced impact from stressors (Braithwaite and Salvanes, 2005;Naslund et al, 2013;Batzina et al, 2014), improved foraging ability (Brown et al, 2003;Strand et al, 2010;Rodewald et al, 2011), improved post-release survival (D'Anna et al, 2012) and positive effects on growth (Leon, 1975;Hansen and Moller, 1985;Batzina et al, 2014). This general increase in neural plasticity results in the development of behaviourally flexible fish that are better at coping with a variety of situations.…”
Section: Introductionmentioning
confidence: 99%